PAKOM APLIKASICOOPERATIVE LEARNING UNTUK PEMBELAJARAN BAHASA INGGRIS DI SMA DAN SMK MUHAMMADIYAH SE-SURAKARTA - Muamaroh, Muamaroh (WARTA, 2015)
The objective of this community serves is to give a workshop to English teachers using cooperative learning method in particular the techniques of Student Teams Achievement Division (STAD), Team-Games-Tournaments (TGT) andJigsaw STAD. This activity is also to enhance the quality of teachers in language teaching method in the class. Cooperative learning is teaching method using small group which provide students to help each other to discuss and understand lessons given by their teacher. The subject of this activity is English teachers of Muhammadiyah Senior High Schools, and Muhammadiyah Vocational schools in Surakarta. The output of this activity is participants understand and master the techniques that trained to them during the workshop. The teachers perceived that this activity is positive and very beneficial for them. They intended to implement those teaching techniques in their real English classroom.